ANALYSIS OF SOCIOLOGICAL PROBLEMS IN THE WORK OF PROFESSORS AND TEACHERS IN HIGHER EDUCATION INSTITUTIONS IN THE PERIOD OF REFORM OF THE HIGHER EDUCATION SYSTEM IN UZBEKISTAN (Academicia Globe: Inderscience Research, 2021)
One of the sociological problems that needs to be studied today is how the reforms and modernization of the higher education system in our country affect the teaching staff, leadership and students, and to what extent they show their results. We should not be agree about the fact that during the period of change, every professor and head of higher education institution understands the essence of the reforms, the extent to which innovations are reflected in labor and pedagogical activities, attitudes and practices, but all these changes does not find its expression in institutions.